PENGARUH PEMBERIAN CAIRAN INTRAVENA HANGAT TERHADAP KEJADIAN MENGGIGIL PADA PASIEN DENGAN SPINAL ANESTESI DI RSUD KOTA PROBOLINGGO - Pudianto; Tophan Heri Wibowo; Tin Utami (Bajang Institute, 2023)
Spinal anesthesia is one type of anesthesia that is often used in surgery because it is reported to be safe for patients, but that does not mean it is without risks or side effects. One of the side effects is chills. Shivering itself can cause discomfort to the patient during treatment as well as other complications. The aim of the study was to determine the effect of warm intravenous fluids on the incidence of chills in patients with spinal anesthesia at the Probolinggo City Hospital. This research method is quasi-experimental with Posttest Only Control Group Design. Sampling technique with accidental sampling as many as 44 spinal anesthesia patients. Data were taken by measuring the degree of shivering in patients with warm intravenous fluids and room temperature intravenous fluids. The results showed that there was an effect of giving warm intravenous fluids to the incidence of chills in patients with spinal anesthesia at the Probolinggo City Hospital with p value = 0.000. Therefore, warm intravenous therapy has an effect on the incidence of shivering in spinal anesthesia.